Water balance optimization for strategic planting patterns and calendars in paddy (Oryza sativa L.) cultivation in rainfed regions - Yoga, Feri; Simanjuntak, Bistok Hasiholan (Jurnal Ilmiah Pertanian, 2024)
Paddy (Oryza sativa L.) is a staple food crop in Indonesia that requires more water compared to other annual crops. Cultivating paddy in rainfed areas necessitates effective water management to prevent crop failure, making it essential to calculate water balance, planting patterns, and planting calendars. This study aims to analyze the water balance in relation to planting patterns and calendars based on water availability in the field. The research was conducted in Cukilan Village, Semarang Regency, Indonesia. A descriptive quantitative method using Cropwat 8.0 was employed to determine water balance, planting patterns, and planting calendars. The results indicate that from November to April, there is a water surplus, while from May to October, there is a water deficit. Planting can be conducted once per growing season with two possible periods: November-March or December-April. During Period I (November-March), the water requirement is 640.7 mm with effective rainfall of 1031.2 mm. In Period II (December-April), the water requirement is 638 mm with effective rainfall of 935.7 mm. Planting should begin in November or December, with harvest in March or April. From May to October, the land remains fallow due to insufficient water availability. These findings are valuable for enhancing the effectiveness of paddy cultivation in rainfed areas, assisting farmers with planting planning, and minimizing the risk of crop failure due to water scarcity.